The Use of Vibra Engine to Enhance Batako Industrial Quality at Urban Area - Totok Dwi Kuryanto; Irawati Irawati; Nanang Saiful Rizal (Kontribusia : Research Dissemination for Community Development, 2018)
The main objective of the Technology for the Society (IbM) is aimed at addressing the main problems faced by approximately 200 urban poor, namely: (1) The location of the residence located on the edge of the city with a distance society of about 10 km from urban areas. (2) Low economic level or low income about Rp.600.000 / month so it can not meet the basic needs and lift the economy of the surrounding community. The specific target in this IbM program is to apply Batako engine utilization technology to improve the quality and quantity of local Batako production of marginalized urban communities which originally produced only Batako blocks of about 200 seeds to 1000 seeds per day and increased concrete compressive strength. from 175 Kg / cm2 to 225 Kg / cm2, thereby increasing employment for the surrounding communities and increasing the income of business actors and partner workers. The method of implementation to solve the problems of the program partners of IbM is to increase the added value of community income through the utilization of Batako chili type which includes the stages: (a) Thesocialization of Batako IbM program; (b) Preparing social prerequisites, such as strengthening rural community groups, groups and forums as a medium to meet and solve problems faced by farmers or the poor; (c) Implementation of Batako IbM program, supported by related institutions (Dinas Cipta Karya Kabupaten Lumajang and University (Faculty of Engineering, Muhammadiyah University of Jember), and (d) Monitoring, evaluation and reporting.